2015
DOI: 10.3945/ajcn.114.104836
|View full text |Cite
|
Sign up to set email alerts
|

Dietary micronutrient intake during pregnancy is a function of carbohydrate quality

Abstract: Normal pregnancy can be associated with a decline in energy and micronutrient intake from diet. Low dietary GI and GL were the best predictors of a favorable micronutrient profile. This trial was registered at www.anzctr.org.au as ACTRN12610000174088.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 32 publications
2
24
0
3
Order By: Relevance
“…14 The type and quality of carbohydrates consumed during pregnancy has also been associated with dietary micronutrient intakes. 19 In addition, nearly one in five women (18.1%) reported that they did not consume fruits or vegetables at least 2-3 times a day. This standard is substantially lower than what is typically recommended for health, including during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…14 The type and quality of carbohydrates consumed during pregnancy has also been associated with dietary micronutrient intakes. 19 In addition, nearly one in five women (18.1%) reported that they did not consume fruits or vegetables at least 2-3 times a day. This standard is substantially lower than what is typically recommended for health, including during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the proportion of dietary protein from energy intake was relatively appropriate [20]. However, a majority of these women did not achieve the RNI for dietary calcium and iron, which were also reported in other studies [7,27,33]. Adequate iron and calcium are critical for foetal development [34].…”
Section: Discussionmentioning
confidence: 66%
“…Os carboidratos representam a maior proporção de macronutrientes da dieta e são, deste modo, bons fornecedores de micronutrientes. Os carboidratos podem ser avaliados quanto à sua qualidade, de acordo com o índice glicêmico, a carga glicêmica, a quantidade de fibras e de açúcar adicionado 11,16 .…”
Section: Discussionunclassified
“…Em relação ao papel dos carboidratos na adequação do consumo de micronutrientes, foram propostos intervalos de 50%-54% de carboidratos da energia total para uma boa adequação 16 .…”
Section: Discussionunclassified